Choushenosides A-C, three dimeric catechin glucosides from Codonopsis pilosula collected in Yunnan province, China. (September 2018) - Qin, Fu-Ying; Cheng, Li-Zhi; Yan, Yong-Ming; Liu, Bao-Hua; Cheng, Yong-Xian
Abstract: Choushenosides A-C, three dimeric catechin glucosides, were isolated from the roots of Codonopsis pilosula cultivated at high elevations in Yunnan province of the People's Republic of China. The structures of these substances were determined by using spectroscopic and chemical methods. Biological evaluation showed that choushenoside C is a dose-dependent inhibitor of SIRT1. Graphical abstract: Highlights: Three previously undescribed catechin dimer glucosides were isolated from the water extract of Codonopsis pilosula. The absolute configuration of the glucose residue was assigned by GC analysis. Choushenoside C was found to inhibit SIRT1 in a dose-dependant manner.